Pelatihan Manajemen pada Bank Sampah Koperasi Melati Jaya - Nuzul Inas Nabila; Aida Sari; Mirwan Karim; Driya Wiryawan (Jurnal Pemberdayaan Umat, 2022)
Purpose: To increase waste bank management science of knowledge  for members in the Melati Jaya cooperative and to improve and develop waste bank business management at the Melati Jaya cooperative. Method: This activity uses a participatory approach by involving partners in carrying out the stages as described in the activity road map. This activity is carried out by providing education on waste bank management. In the stage of counseling the service team and partners to improve management knowledge, skills and waste bank management. Result: Evaluation of the pre-test and post-test in the delivery of material to the participants of the Melati Jaya cooperative were an increase of 14 percent. The results of this increase in average score indicate an increase in the knowledge of cooperative members participating in training on waste bank management, and continue to motivate participants to continue choosing organic and inorganic starting from households because it can increase income economically.